Translation of the SASIKAP employee performance appriaisal system (SASIKAP) at Bandung Regency Education - Tengku Ine Hendriana; Eliza Viandrayani Aziz; Syaepudin Syaepudin; Janadi Rammelsbergi Thamrin; Tini Martini (Institute of Computer Science (IOCS), 2026)
This study examines the effect of the Sabilulungan Employee Performance Appraisal System (SASIKAP) on performance appraisal activities at the Department of Education of Bandung Regency. Previous studies have primarily focused on employee performance from the perspectives of motivation, competence, leadership, and work discipline, while empirical evidence regarding the effectiveness of digital performance appraisal systems in the public sector remains limited. This study addresses this gap by evaluating the implementation of SASIKAP through a quantitative approach involving 52 employees selected using probability sampling. Data were collected through questionnaires, observations, and interviews and analyzed using simple linear regression. The results indicate that SASIKAP has a significant positive effect on performance appraisal (t = 5.159 > t-table = 2.009, p < 0.05). The correlation coefficient (R = 0.589) indicates a moderate positive relationship, while the coefficient of determination (R² = 0.347) shows that SASIKAP explains 34.7% of the variance in performance appraisal activities, with the remaining 65.3% influenced by other factors. The novelty of this study lies in providing empirical evidence of a government-specific digital performance appraisal system. The findings contribute to digital human resource management literature and offer practical recommendations to improve system reliability, user competence, transparency, and accountability.